THERAPEUTIC EFFECTS OF Cratargus azarolus VAR. aronia IN UROLITHIATIC MALE ALBINO RATS : Research Article - Khdhr, Aveen R.; Mahmud, Sarbast A. (Science Journal of University of Zakho, 2023)
The study was designed to investigates the therapeutic roles of Crataegus azarolus Var. aronia L. (C. aronia) in kidney stone treatment male albino rats’ model induced by ethylene glycol (EG). Twenty animals weighing 220–270 g were divided into control group which set as group A, while the rats in B and C groups, received 1% EG for 28 days, but group C also received C. aronia (7.5g of plant/100ml water and 10g of plant/ 90 g diet) from day 15 to 28. Kidney function tests, liver function tests, serum electrolytes, serum lipid profiles, and glucose were measured. The obtain body weight, kidneys’ weight and kidneys’ weight/ body weight were measured, in addition microscopic analysis of formed crystals from urine was studied. Crataegus aronia administration showed a marked declination in serum creatinine, urea, cholesterol, triglyceride (TG), very low-density lipoprotein (VLDL), and non-high density lipoprotein cholesterol (non-HDL cholesterol) inverse to rats received EG. Also, the obtain body weight, kidneys’ weight and kidneys’ weight/ body weight markedly decreased in C group when compared to group B. In conclusion: C. aronia has clear therapeutic actions on formed kidney stone might be used employee as natural antiurolithiasis drug.